"Meta-Talk" as a Composition Tool: Promoting Reflective Dialogue During the Drafting Process. (2nd October 2017) - Song, Ah-Young
Abstract: This article argues for expanded opportunities for metalinguistic dialogue and written response rounds in order to better understand students' needs. Encouraging students to reflect on their compositions can invite multiple stylistic approaches and inform a more participatory composition process. The writing explores theoretical underpinnings, makes a case for metalinguistic dialogue, and remarks on the use of written exchanges between students and teachers.